Transcendental Naturalism, New Materialisms, and Emerging Planetary Values - Bauman, Whitney A. (Zygon, 2025)
In recent decades, modern Western scholars have done a lot of work to develop an understanding of nature that is agential and animated. Emergence theories, new materialisms, neo-animisms, and post-humanisms are just some of the names used to describe these types of ontologies. Arthur Petersen’s “transcendental naturalism” is another excellent example of these understandings of nature reanimated. Of course, these “new” materialisms are not so new and have much to learn from older romanticisms, animisms, and so-called relational ontology. In this brief commentary, I look at some of the issues that arise when doing science from a “productive reductive” understanding of nature versus some type of what Dalia Nassar calls “Romantic Empiricism.” I then offer ideas about how we might derive some sort of ethics from these so-called “flat” ontologies.